2019
DOI: 10.1038/s41467-018-08126-5
|View full text |Cite
|
Sign up to set email alerts
|

C1 CAGE detects transcription start sites and enhancer activity at single-cell resolution

Abstract: Single-cell transcriptomic profiling is a powerful tool to explore cellular heterogeneity. However, most of these methods focus on the 3′-end of polyadenylated transcripts and provide only a partial view of the transcriptome. We introduce C1 CAGE, a method for the detection of transcript 5′-ends with an original sample multiplexing strategy in the C1TM microfluidic system. We first quantifiy the performance of C1 CAGE and find it as accurate and sensitive as other methods in the C1 system. We then use it to pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…New technologies, such as single cell sequencing, will allow annotation of cell-specific expressed and regulatory regions of the genome at unprecedented resolution (Papatheodorou et al, 2019). C1 CAGE now offers the opportunity to detect TSS and enhancer activity at single-cell resolution (Kouno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…New technologies, such as single cell sequencing, will allow annotation of cell-specific expressed and regulatory regions of the genome at unprecedented resolution (Papatheodorou et al, 2019). C1 CAGE now offers the opportunity to detect TSS and enhancer activity at single-cell resolution (Kouno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recent single-cell genome-wide data of nascent transcription challenges some of the typical characteristics of eRNAs as it was shown that enhancer transcription is unidirectional, and therefore within a cellular population, some cells transcribe the sense strand and others the antisense strand. 15 In the cases where both strands of eRNAs were detected in the same cell, single-molecule fluorescence in situ hybridization (FISH) experiments showed that colocalization of both RNA molecules was rare. Because typical RNA expression methodologies show an average for total cells, that would explain why eRNAs have been described as bidirectional.…”
Section: General Features and Dynamics Of Ernasmentioning
confidence: 99%
“…Importantly, eRNAs were expressed at similar levels compared with gene promoters in single cells and were detected in just a subset of cells, ie, displaying transcriptional bursting. 15 More single-cell measurements of nascent transcription in different conditions are needed to clarify the real nature of transcripts originating from enhancers.…”
Section: General Features and Dynamics Of Ernasmentioning
confidence: 99%
“…The t-SNE plot in the middle panel of ( Fig. 5a In the single-cell dataset PRJDB5282 [13], generated by C1 CAGE protocol ( Fig. 5c), the skewed cells clustered separately on t-SNE plot (top of Fig.…”
Section: Effect Of Skewed Cells On Downstream Analysismentioning
confidence: 99%
“…1c). The tag-based sequencing of 5' or 3' ends methods [11][12][13][14] should have the peak coverage at either the 5' or 3' end of the gene with low/no coverage in the middle region of the gene body. In the second type, there was high coverage in the middle of the gene for 5'-end and 3'-end sequence protocols (Fig.…”
mentioning
confidence: 99%